GE_GERICHTE P/3441/2019 vom 2. Mai 2019 - GE Cour de justice (2019)
RÉVISION(DÉCISION) CIRCULATION ROUTIÈRE(DROIT DE LA CIRCULATION ROUTIÈRE) ; CONTRAVENTION | LCR.93.al2; LCR.29; OETV.58; OETV.59; OETV.60; CPP.410.al1.leta; CPP.413.al2.letb; CPP.415.al2